Membangun Kepekaan Gender di Lingkup Perguruan Tinggi - Jiwanda DL, Jatayu (International Journal of Demos (IJD), 2023)
Abstract                                       This research contains reflections and analysis of research on building gender sensitivity within Sriwijaya Buddhist College. Gender issues are important considering the urgency of gender equality must continue to be pursued, especially in the scope of higher education. Gender sensitivity is important to become the mentality of each academic community so that gender injustice and discrimination can be avoided in the implementation of campus life activities. With gender sensitivity we become aware not to make or even criticize stereotypes that imply injustice or inequality as an assumption that should be done or a truth. With campus academic community informants, exposure is obtained regarding the forms and attitudes that can be a reference for building gender sensitivity in the campus environment. This type of research is descriptive qualitative through observation, interviews and documentation which will obtain an overview of the meaning, forms and attitudes needed to build gender sensitivity in the campus environment.Keywords:  gender, sensitivity, equality AbstrakPenelitian ini berisi tentang refleksi dan analisis penelitian membangun kepekaan gender di lingkup kampus STABN Sriwijaya. Isu gender adalah hal yang penting mengingat urgensi kesetaraan gender haruslah terus diupayakan khususnya dalam lingkup perguruan tinggi. Kepekaan gender penting menjadi mentalitas masing-masing sivitas akademik sehingga ketidakadilan maupun diskriminasi gender dapat dihindarkan dalam pelaksanaan kegiatan kehidupan kampus. Dengan kepekaan gender kita menjadi sadar untuk tidak menjadikan atau bahkan mengkritisi stereotipe yang menyiratkan ketidakadilan atau ketimpangan sebagai anggapan yang seharusnya dilakukan atau sebuah kebenaran. Dengan informan sivitas akademik kampus, maka diperoleh paparan mengenai bentuk dan sikap yang dapat menjadi acuan untuk membangun kepekaan gender di lingkup kampus. Jenis penelitian ini adalah kualitatif deskriptif melalui observasi, wawancara dan dokumentasi yang nantinya memperoleh gambaran mengenai makna, bentuk-bentuk dan sikap yang diperlukan untuk membangun kepekaan gender di lingkup kampus.Kata kunci: gender, kepekaan, kesetaraan.